2016
DOI: 10.1103/physreva.94.042114
|View full text |Cite
|
Sign up to set email alerts
|

Non-Markovianity in atom-surface dispersion forces

Abstract: We discuss the failure of the Markov approximation in the description of atom-surface fluctuationinduced interactions, both at equilibrium (Casimir-Polder forces) and out-of-equilibrium (quantum friction). Using general theoretical arguments, we show that the Markov approximation can lead to erroneous predictions of such phenomena with regard to both strength and functional dependencies on system parameters. Our findings highlight the importance of non-Markovian effects in dispersion interactions. In particula… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
70
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(77 citation statements)
references
References 109 publications
(193 reference statements)
7
70
0
Order By: Relevance
“…This means that D H n ≈ D lc n reduces to the local Drude result D lc n reported in Ref. [46] and we obtain for the quantum frictional force experienced by an atom in the half-space geometry…”
Section: Conclusion and Discussionsupporting
confidence: 79%
See 2 more Smart Citations
“…This means that D H n ≈ D lc n reduces to the local Drude result D lc n reported in Ref. [46] and we obtain for the quantum frictional force experienced by an atom in the half-space geometry…”
Section: Conclusion and Discussionsupporting
confidence: 79%
“…This constraints the validity of the linear regime of the extended hydrodynamic model to frequencies ω r TM I (Γ, p)/(2 0 ρ eH (p)) (p λ −1 TF ), where ρ eH is the respective resistivity. Since the frictional force on atoms is dominated by frequencies ω p · v and for the planar geometry we have that p ∼ z −1 a [46], we conclude that the Ohmic response of the extended hydrodynamic model holds for velocities (see Fig. 4)…”
Section: A a Nonlocal Infinite Half Spacementioning
confidence: 63%
See 1 more Smart Citation
“…The bosonic operators satisfy the commutation relation [â kω ,â † k ω ] = δ(k − k )δ(ω − ω ) creating and destroying "photons" in a wider meaning, since they are creation and destruction operators of composite states (field plus material). In particular, it has been shown that [50]…”
Section: The Modelmentioning
confidence: 99%
“…While there has been a large number of studies on the static CP force (see, e.g., [14]- [15] and references therein), studies of the transient CP force have been limited in scope (e.g., in [15] a Jaynes-Cummings, single mode field is assumed in the strong coupling case). And, there have been few studies of the non-Markovian CP force [16]. In this work, we consider the initial-value problem of introducing either an excited or a ground state atom into an environment at t = 0, which is a special case of the Dynamical Casimir Effect, which also encompasses photon generation from fast changes in geometry [17].…”
Section: Introductionmentioning
confidence: 99%